Pencegahan Kejahatan Fungsi Bhabinkamtibmas Terhadap Tingkat Kesadaran Hukum Kasus Carok Pada Pemilihan Kepala Desa Dikaitkan Dengan Harga Diri Kolektif Masyarakat - Haris, Afrizal Akbar; Prisgunanto, Ilham; Sinaga, Saut Panggabean (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2024)
The problem of "carok" due to disputes over village head elections in Madura society has not been resolved despite being recognized as illegal. Efforts are needed to increase the legal awareness of the community in resolving conflicts more wisely without losing the collective self-esteem of the community. The presence of police officers in the community, namely Bhabinkamtibmas, is expected to act as mediators in building legal awareness. The aim of this research is to analyze the effectiveness of crime prevention through the implementation of Bhabinkamtibmas functions in increasing Legal Awareness for Preventing "Carok" in Village Head Elections Moderated by the Collective Self-esteem Values of Madura Society. This research is observational. The research variables are the efficiency of the implementation of Bhabinkamtibmas's main tasks and functions, legal awareness, prevention of carok in village head elections, and the collective self-esteem values of the community. The population is the community of Bangkalan with a sample size of 200 people taken using purposive sampling technique. Data collection tools use questionnaires and are analyzed using regression. Partially, the implementation of crime prevention by Bhabinkamtibmas effectively increases legal awareness among the community. The legal awareness possessed by the community significantly influences the prevention of carok due to village head election activities. The effectiveness of crime prevention by Bhabinkamtibmas functions and Legal Awareness together affects the prevention of carok in village head elections with the moderation of the collective self-esteem of the community. The culture of carok due to conflicts in village head elections must be ended as it causes the loss of other people's lives and leads to punishment. The role of Bhabinkamtibmas needs to be enhanced.